(untitled) (EU and comparative law issues and challenges series (ECLIC), 2022)
Over the last two decades, a better digital transformation has fundamentally changed the global economy and society. Digital services have become new tools and their importance for our social and economic life will continue to grow. When we adopted the e-commerce directive 20 years ago, many digital services and platforms such as Google, Amazon or Booking were in their initial stage or did not yet exist. The blockades as the consequence of the COVID pandemic have now strengthened the role of online platforms. People have changed their habits towards the online world so that they can do business, shop, work, learn and socialize. COVID-19 has led to an increase in online e-commerce and an increase in fraud, unfair practices, and other illegalities of various formats. The crisis has exposed the system’s existing gaps and weaknesses, which has allowed dishonest services and traders to exploit people’s current insecurity. The Commission has proposed an ambitious reform of the digital space, a comprehensive set of new rules for all digital services, including social media, online marketplaces and other online platforms operating in the European Union: The Digital Services Act and The Digital Markets Act. In this article, we will look at the Commission’s proposal for The Digital Markets Act (DMA), which was published on December 15, 2020. In the last few years, it has been concluded that a small number of large digital platforms act as “gatekeepers” because they are essential gateways between business users and their potential customers. This allows these platforms to take advantage of the enterprise users’ dependence on their services by imposing unfair business conditions. As this issue may not be adequately addressed in competition law, it has led the European Commission to propose a Digital Markets Act (DMA). The DMA should introduce more flexibility and adaptability in terms of imposing the “gatekeeper” obligations. In this article, we will focus on the question of which digital platforms should be subject to ex ante regulation, and thus also the obligations contained in the DMA proposal. The methodology used to identify the “gatekeepers” cannot be separated from the problems that ex ante regulation seeks to address, as otherwise the DMA could end up regulating the wrong set of companies. The DMA proposal describes “gatekeepers” as providers of the core platform service (CPS) that meet three cumulative quality criteria. These criteria are presumed to be met if the relevant CPS provider meets the quantitative size thresholds. DMA includes a mechanism that allows CPS providers who meet these quantitative thresholds to escape labelling. This article reveals the various provisions of the DMA and explains why the Commission has decided to regulate “gatekeepers” and how it can prevent the damage caused by large digital platforms.